IMPLEMENTASI MODEL PEMBELAJARAN DIRECT INSTRUCTION DALAM PEMBELAJARAN SENI TARI (STUDI KASUS PENINGKATAN MINAT SISWA LAKI-LAKI DALAM PEMBELAJARAN SENI TARI DI SEKOLAH DASAR): STUDI KASUS PENINGKATAN MINAT SISWA LAKI-LAKI DALAM PEMBELAJARAN SENI TARI DI SEKOLAH DASAR - Khadijah, Ananda Arjuni; Shanie, Arsan (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Abstract This study aims to describe how the implementation of the direct instruction learning model in learning the art of dance to increase the interest of male students in elementary schools. This research is a qualitative research with a descriptive approach. Informants in this study were school principals, grade 4 teachers, and male students of grade 4 SD N Bangunharjo Semarang. Data collection techniques using observation, interviews, and documentation. The validity of the data is done by triangulation of techniques and sources. The data analysis technique used is data reduction, data presentation, and drawing conclusions. The results of this study used 3 phases of direct instruction learning, namely direct learning planning, direct learning implementation and evaluation based on direct learning. The direct instruction learning model succeeded in attracting the interest of grade 4 male students at SD N Bangunharjo in learning the art of dance after a learning evaluation was carried out. At first, male students felt shy, unenthusiastic, unfocused, and talked to their friends, which made studying less efficient. Male students participate more in class with the direct instruction learning paradigm. Keywords: Direct Instruction, Interest, Learning the art of dance